Hegel’s concept of Absolute in Differenz-Schrift (1801) and the speculative transformation of Metaphysics - Profili, Lelia Edith (Pensamiento. Revista de Investigación e Información Filosófica, 2025)
Contrary to the interpretation which finds in the first works of Hegel during the Jena period an `ontological concept of Absolute” (K. Düsing, 1988), this paper aims to show they lay the foundation of the subsequent Hegelian project and that the intention of connecting Logic and Metaphysics is already present. The novelty of the "identity of identity and non-identity" thought, against Schelling's duplicate identity principle, provides reliable proof of the stated thesis, confirming the direct relationship of the Hegelian concept of Absolute with the logic-speculative transformation of Metaphysics. Such verification will allow for the defense that the doctrine formulated by Hegel in that period does not circumscribe to a mere ontology of substance.
Keywords: absolute; Hegel; German Idealism; speculative logic; metaphysics